Adipocyte Angptl8 deletion improves glucose and energy metabolism and obesity associated inflammation in mice - Anindya Ghosh; Isabelle Chénier; Yat Hei Leung; Abel K. Oppong; Marie-Line Peyot; S. R. Murthy Madiraju; Irina Al-Khairi; Jehad Abubaker; Fahd Al-Mulla; Marc Prentki; Mohamed Abu-Farha (iScience)
Summary: Angiopoietin-like protein 8 (Angptl8), expressed in the liver and adipocytes, forms a complex with Angptl3 or Angptl4, which regulates lipoprotein lipase and triglyceride metabolism. However, the precise functions of adipocyte Angptl8 remain elusive. Here we report that adipocyte-specific inducible Angptl8-knockout (AT-A8-KO) male mice on normal diet showed minor phenotypic changes, but after a high-fat high fructose (HFHF) diet, exhibited decreased body weight gain and glycemia, elevated rectal temperature and early dark phase energy expenditure compared to the Cre controls. AT-A8-KO mice also displayed improved glucose tolerance, a trend for better insulin sensitivity, improved insulin-stimulated glucose uptake in adipose tissues, and reduced visceral adipose tissue crown-like structures, plasma MCP-1 and leptin levels. The results indicate the importance of adipose Angptl8 in the context of nutri-stress and obesity, as its deletion in mice promotes a metabolically healthy obese phenotype by slightly ameliorating obesity, improving glucose and energy homeostasis, and mitigating inflammation.